Clip stopper closure method using a detachable snare in combination with ZEOCLIP for endoscopic submucosal dissection‐induced mucosal defects. Issue 1 (29th August 2022) - Hamada, Shohei; Ihara, Eikichi; Yoshitake, Chikako; Inada, Taisuke; Fukuya, Hiroki; Ohkubo, Akito; Tomoeda, Naru; Iboshi, Yoichiro; Sumida, Yorinobu; Yoshimura, Daisuke; Nakamuta, Makoto; Harada, Naohiko
Abstract : Endoscopic submucosal dissection (ESD) is globally performed to treat early epithelial tumors of the gastrointestinal tract, but delayed perforation is a problematic procedure‐related complication. To address this problem, closure of ESD‐induced mucosal defects with a detachable snare has been reported. However, one problem is that this method usually requires some degree of skill and replacing a single‐channel scope with a two‐channel scope. We developed the clip stopper closure (CSC) method using a detachable snare in combination with the ZEOCLIP, which can be easily performed with a single‐channel scope, for ESD‐induced mucosal defects. Six consecutive cases were treated with this closure method for colonic ESD‐induced mucosal defects. The median closure time was 12.5 (10–24) min, and the success rate of this procedure was 100%. Our CSC method was able to be performed in any part of the colon. In conclusion, the CSC method using a detachable snare in combination with the ZEOCLIP is a simple but promising closure technique for ESD‐induced mucosal defects.